1-year cost-utility analysis of prostate artery embolization (PAE) versus transurethral resection of the prostate (TURP) in benign prostatic hyperplasia (BPH) - Mark Harris; Nikisha Patel; Bhaskar Somani; Nigel Hacking; Timothy Bryant; Nathan Yung; Ganesh Vigneswaran; Laure de Preux; Drew Maclean; Sachin Modi (BMJ Surgery, Interventions, & Health Technologies, 2021)
Objective To determine whether prostate artery embolization (PAE) is a cost-effective alternative to transurethral resection of the prostate (TURP) in the management of benign prostate hyperplasia (BPH) after 1-year follow-up.Design, setting and main outcome measures A retrospective cost-utility analysis over a 12-month time period was conducted to compare the two interventions from a National Health Service perspective. Effectiveness was measured as quality-adjusted life years (QALYs) derived from data collected during the observational UK Register of Prostate Embolisation (UK-ROPE) Study. Costs for both PAE and TURP were derived from University Hospital Southampton, a tertiary referral centre for BPH and the largest contributor to the UK-ROPE. An incremental cost-effectiveness ratio (ICER) was derived from cost and QALY values associated with both interventions to assess the cost-effectiveness of PAE versus TURP. Further sensitivity analyses involved a decision tree model to account for the impact of patient-reported complications on the cost-effectiveness of the interventions.Results The mean patient age for TURP (n=31) and PAE (n=133) was 69 and 65.6 years, respectively. In comparison to TURP, PAE was cheaper due to shorter patient stays and the lack of necessity for an operating theatre. Analysis revealed an ICER of £64 798.10 saved per QALY lost when comparing PAE to TURP after 1-year follow-up.Conclusion Our findings suggest that PAE is initially a cost-effective alternative to TURP for the management of BPH after 1-year follow-up. Due to a higher reintervention rate in the PAE group, this benefit may be lost in subsequent years.Trial registration number NCT02434575.